Understanding stress in the healthy animal -potential paths for progress. - Romero, L. Michael.; Platts, Steven H.; Schoech, Stephan J.; Wada, Haruka.; Crespi, Erica.; Martin, Lynn B.; Buck, Charles Loren. (Tufts University. Tisch Library., 2016)
Although stress is usually associated with disease, the physiological and behavioral responses to stressors are critical mechanisms of resilience for healthy organisms. A recent workshop comprised of researchers who study healthy humans and both free-living and captive non-human animals identified a number of key roadblocks that are impeding progress in understanding how stress responses integrate into the normal physiology of an animal. These include the lack of: (1) an unambiguous definition of a stress phenotype; (2) a robust biomarker, or suite of biomarkers, to indicate that phenotype; (3) theoretical and quantitative models to predict how humans and other animals will react to stressors; (4) a comprehensive understanding of how individual variability in stress responses arise and (5) an understanding of the transitions between acute and chronic stress responses. Collectively, these deficiencies impair our ability to both assess the physiological status of individuals and develop procedures and techniques to reverse the effects elicited by chronic stress before they become pathological. Workshop participants also identified a number of potential approaches to facilitate progress on these problems. They include: (1) increased use of mathematical models to provide quantitative predictions; (2) use of network theory to expose emergent properties not predicted from traditional approaches; (3) development and deployment of improved sensor technology that will allow long-term, dynamic, non-invasive, multi-factor measurements of suites of stress mediators and (4) the recruitment of scientists with diverse skill sets, such as engineers, bioinformaticians, etc.; and (5) the training of young scientists in the multidisciplinary study of stress. Incorporating these approaches in new research should reinvigorate the study of stress and stimulate progress in understanding both how healthy humans cope with stressors and how other animals, including free-living animals, cope with stressors in a rapidly changing environment.